The Effect of Tax Morale on the Compliance of Rural and Urban Land and Building Taxpayers: A Study of the Kaili Tribe in Palu City with Nosarara Nosabatutu Culture as a Moderating Variable - Giska Darmayanti; Ni Made Suwitri Parwati; Muhammad Bashri Bas (Journal GoodWill, 2025)
This study investigates the influence of tax morale on the compliance of Rural and Urban Land and Building Taxpayers (PBB-P2) in Palu City, with the Nosarara Nosabatutu culture acting as a moderating variable. Taxpayer non-compliance remains a persistent issue in Palu, reflected in fluctuating and relatively low levels of PBB-P2 realization compared to annual targets. Despite governmental efforts to strengthen tax administration, socio-cultural aspects influencing taxpayer behavior have received limited empirical attention. Using a quantitative approach, this study employed purposive sampling to select 399 taxpayers of Kaili ethnicity, and data were collected through structured questionnaires supported by observation and documentation. The analysis was conducted using Moderated Regression Analysis (MRA) via SPSS. The findings reveal that tax morale has a positive and significant effect on taxpayer compliance, indicating that taxpayers with stronger moral awareness are more likely to fulfill their tax obligations. Additionally, the Nosarara Nosabatutu culture significantly moderates this relationship by strengthening the effect of tax morale on compliance. This cultural value—emphasizing kinship, unity, and shared responsibility—enhances the internal motivation of taxpayers to act responsibly. The study highlights the importance of integrating cultural approaches into tax compliance strategies and suggests that policymakers consider local wisdom in designing tax education and socialization programs. These results contribute to the behavioral tax literature by demonstrating the relevance of cultural values in shaping taxpayer compliance in diverse local contexts.